2019
DOI: 10.1177/0269216319854938
|View full text |Cite
|
Sign up to set email alerts
|

Video consultations in palliative care: A systematic integrative review

Abstract: Background: There is extensive need for palliative care worldwide, but access to care remains inadequate, especially for non-cancer patients. Video consultations are a promising tool in the provision of home-based palliative care, but an overview of evidence solely on video consultations in palliative care is lacking. Aim: To review and synthesize current evidence regarding the use of video consultations in general and specialized palliative care to various patient groups. Design: A systematic integrative revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 61 publications
(458 reference statements)
4
120
0
3
Order By: Relevance
“…In this review, several themes emerged with respect to the advantages and disadvantages of using videoconferencing in PC including the redesign of care; communication among patients, family members, and the clinicians; users' perceptions of video consultations; technology issues; privacy concerns; and economic considerations. 14 As our study progresses, other potential challenges may include how PC clinicians address sensitive topics with patients and families through telehealth, including discussions about preferences for EOL care and advance care planning. Although some research is beginning to take place on telephonic discussions of advance care planning, 31 further study is needed to discern the best practices for such conversations using videoconferencing to ensure patients and families have accurate understanding of their illness and sufficient support to communicate their goals and wishes.…”
Section: S-16mentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, several themes emerged with respect to the advantages and disadvantages of using videoconferencing in PC including the redesign of care; communication among patients, family members, and the clinicians; users' perceptions of video consultations; technology issues; privacy concerns; and economic considerations. 14 As our study progresses, other potential challenges may include how PC clinicians address sensitive topics with patients and families through telehealth, including discussions about preferences for EOL care and advance care planning. Although some research is beginning to take place on telephonic discussions of advance care planning, 31 further study is needed to discern the best practices for such conversations using videoconferencing to ensure patients and families have accurate understanding of their illness and sufficient support to communicate their goals and wishes.…”
Section: S-16mentioning
confidence: 99%
“…10 Studies show that telehealth not only increases access to health care services, especially where the availability of specialty clinicians is limited, but also is equivalent to in-person services for mental health, rehabilitation, and dermatology. 11,12 Although researchers are beginning to study the use of videoconferencing to conduct virtual home visits in the context of providing PC, 13,14 prior studies have demonstrated that telephone-based psychoeducational interventions, delivered by PC-trained advanced practice nurses, improve QOL and lower depression symptoms among patients with newly diagnosed advanced cancers as well as decrease depression symptoms in their caregivers. 15,16 Telehealth may be especially helpful for caregivers by improving access to PC for patients' loved ones, enhancing communication between multiple family members and the care team, and reducing the burden of attending in-person clinic visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews have indicated that telemedicine can be useful within palliative care. Most users are positive about the use of technology in palliative care [9,10]. Telemedicine might provide a feeling of security and contribute to building trust between patients, relatives and healthcare providers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most users are positive about the use of technology in palliative care [9,10]. Telemedicine might provide a feeling of security and contribute to building trust between patients, relatives and healthcare providers [9,10]. The provision of specialized palliative care at home is both desired and needed and may contribute to avoiding unwanted hospitalization at the end of life.…”
Section: Introductionmentioning
confidence: 99%